Pemanfaatn tandan kosong kelapa sawit (Elaeis guinensis jacq) sebagai biopot ramah lingkungan - Eko Sutrisno; Thamrin Thamrin; Bintal Amin (Jurnal Zona, 2017)
The use of polybag in nursery had an impact on the environment due to the plastic bag waste. Beside carrying environmental pollution, the use of plastic polybag can damage plant root during planting time. This research aimed at making environmentally friendly biopot from the mix of palm oil fruit bunches and the second hand cardbox using organic adhesive. The experimental used completed random factorial design with three time repititions. The first factor was the PVAc (polyvinyl acetate), citrate acid + sucrose and tanin. The second factor was the mix composition of palm oil fruit bunches and second cardbox. The pulping process of empty palm oil fruit bunches produced yield by 90.95 % and second cardbox by 86,67 %. The test showed that biopot produced of value water content by 1,05-15,54 %, gramatur 0,22-0,41 g/cm2, water absorption 1,72 – 2,63%, expand of thickness 0,26 -  15,58 % and burst pressure by 5,33 – 36,67 Kg. Biopot is able to contribute of nitrogen nutrient by 0,440 – 1,080 %, phosphorus nutrient by 0,020 – 0,064 %, and calium nutrient by 0,008 – 0,056 %. The mix mechanism of nutrient in decomposition process. Fastest rate of it was 1 year 9 month and 9 days, while the longest was 2 years, 11 month and 5 days. The produce of biopot can mitigate polybag at 4.217 to to provide 1 billion seed.The treatment of material composition and adhesive types had significant influence on the biopot. From this research it can be concluded that the best formulation for biopot is the composition of 80 % oil palm empty fruit bunches and 20 % second cardbox with the use of tanin adhesive.